Profile of professional home caregivers of senior citizens from a Southern Brazil setting (Research, Society and Development, 2020)
Objective: to describe the social, demographic and professional profile of formal home-based caregivers of elders from a capital city in Southern Brazil.  Method: It is a descriptive, cross-sectional, quantitative study. 50 formal caregivers, who worked at their clients’ homes, were included. The participants were recruited by means of the “snowball” technique, in which a caregiver recommended another. Data collection was held within a pre-assigned period of six months, using a structured questionnaire with 13 questions, comprising social, demographic and professional data, motivation to have such a job, and caregiving experience of older family members. Results: From a total of 50 caregivers, 92% were female gender, mean age of 47.7 years, 76% with concluded high school; 50% attended a caregiving course for senior citizens; 52% were not formally employed; mean working week of 50.6 hours; 64% with salaries ranging up to two minimum salaries. Prevalent motivation to start in the job was the increase in the job market demand. Conclusion: Most caregivers in this study are women, over 40 years of age, who concluded high school, and have worked as paid caregivers of elders for less than ten years. They work for long hours, earning up to two minimum salaries.